PERFORMANCE ANALYSIS OF DIGITAL OVER CURRENT RELAYS UNDER DIFFERENT FAULT CONDITIONS IN RADIAL AND PARALLEL FEEDERS - Sujatha, K. Naga; DurgaRao, R; Shalini, V B (MATTER: International Journal of Science and Technology, 2017)
The conventional relays like electromechanical relays, static and microprocessor based digital relays are having their own disadvantages. Digital/ numeric relays are replacing to overcome these drawbacks. Digital protection devices are built with integrated functions and operated using digital binary values. Fast operation, high sensitivity, self-monitoring, low maintenance are the characteristics of the digital/ numeric relays and their cost is also relatively low. Accuracy, flexibility, reliability, multi-functional capability, and working under wide range of temperatures are the advantages of these relays. They have few limitations such as complexity, short life time due to the new technological developments, and susceptibility to power system transients. Digital over Current relays modeling for power system protection has been proposed in this paper. The performance of the proposed relays was tested by applying different types of fault conditions in radial and parallel feeders and results were analyzed. MatLab/Simulink software was used to simulate the proposed protection scheme due to its features like design flexibility and exploration of any physical module.